2021
DOI: 10.3389/fbioe.2021.658568
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium acetobutylicum Biofilm: Advances in Understanding the Basis

Abstract: Clostridium acetobutylicum is an important industrial platform capable of producing a variety of biofuels and bulk chemicals. Biofilm of C. acetobutylicum renders many production advantages and has been long and extensively applied in fermentation. However, molecular and genetic mechanisms underlying the biofilm have been much less studied and remain largely unknown. Here, we review studies to date focusing on C. acetobutylicum biofilms, especially on its physiological and molecular aspects, summarizing the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…This transitional period requires that cells undergo multiple physiological changes depending on environmental conditions. Cells need to cease growth, initiate spore formation, and/or produce large-scale macromolecular aggregate structures on which cells can maintain a vegetative stage, including biofilm formation ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…This transitional period requires that cells undergo multiple physiological changes depending on environmental conditions. Cells need to cease growth, initiate spore formation, and/or produce large-scale macromolecular aggregate structures on which cells can maintain a vegetative stage, including biofilm formation ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the reason may be that the reabsorption capacity of organic acids was enhanced and the harmful substances around C. acetobutylicum were reduced with adsorption carriers. In addition, C. acetobutylicum can interact with the adsorption carrier to form a cross-linked structure to promote the formation of the cell membrane, improving the tolerance of the strain [ 18 ]. These results showed that the closed circuit and adsorption carrier had a positive effect on fermentation performance.…”
Section: Resultsmentioning
confidence: 99%